Pendidikan Karakter dalam Membangun Mentalitas Disiplin Anak Didik - I Nyoman Temon Astawa; Ni Wayan Sukerti (Jurnal Pendidikan Agama, 2021)
Education is a process of humanizing humans, namely a process that is able to realize a complete human being, raise awareness to recognize, understand, and understand the reality of life around him. According to Law Number 20 of 2003 concerning the National Education System, the function and purpose of developing capabilities and shaping the character and civilization of a dignified nation is to develop the potential of students to become human beings who believe and are devoted to God Almighty, have noble character, are healthy, and have good morals. knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. To achieve this goal cannot be separated from the participation of parents or family. The family is part of the social structure of every society and is one of the earliest social elements to be impacted by any socio-cultural change. Education in general aims to develop human resources that are intact and reliable, but are often very idealistic and without direction so that they are less relevant to the needs in the field. National education functions to develop and shape the character and civilization of a dignified nation in the intellectual life of the nation. Meanwhile, the purpose of national education is to develop the potential of students to become human beings who are knowledgeable, devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens. Therefore we need a man who is tough, reliable, intelligent, and has a competitive character. Thus, a creative learning is needed to produce creative, skilled, and characterized human beings. Implementation of character education, including; The application of character education in the implementation of learning is carried out using a contextual approach strategy. Development of school culture and the center of learning activities is carried out through self-development activities, namely routine activities, spontaneous activities, exemplary, and conditioning. Enabling co-curricular and extra-curricular activities which are activities outside of learning activities. Intensifying positive activities in the family and community environment, as well as in the school environment.